Neuroticism and sport: How personality affects lifestyle in the UK - Rowan Cherodian; Adelina Gschwandtner; Sarah L. Jewell; Uma S. Kambhampati (University of Kent, School of Economics, 2022)
In recent years, researchers have become increasingly aware of the impact that personality traits have on individual lifestyle decisions, both positive and negative. Using longitudinal data from a large household survey as well as genetic information from the UK, the present study unveils the causal relationship between neuroticism as a personality trait and sports activity. Our results suggest that neuroticism leads individuals to perform less sports activities. While this result is intuitive, our method establishes causality and draws attention to the difficulty of policy in this area. In particular, one of the main ways recommended to help improve neuroticism is exercise but our results indicate that neurotic individuals are less likely to take up sporting activity. In this context, tailoring lifestyle recommendations to personality would significantly improve their results and help increase the efficacy of health policy. This is important to reduce the economic burden of ill health.
Keywords: I12; I14; I31; C18; D91; Z20; 330; Big5 Personality Traits; Neuroticism; Exercise; Lifestyle; Personalized Medical Care